A study on the requirement, criteria and factor of university student for entering future market based on personal development scope / Asriza Saari and Marliana Rosidey - Saari, Asriza; Rosidey, Marliana (Faculty of Administrative Science and Policy Studies, 2012)
Personal development is an important element that each individual should carry. It is because personal development will help people to improving themselves. Personal development is the study and practice to improving one’s life especially in our career education, relationship, health, happiness, productivity, spirituality and other personal goals. The common aspects of personal development are including the goal setting, motivation, improving the awareness, values, belief and also self actualization. People will need to continuously develop their personal since humans will become conscious to pursue on their happiness and satisfaction. From the personal development people will also learn lot about the different ways to improve lives. There are many ways can be use to improve the self improvement goals. People also can develop their personal internally or externally through learning from others experience, seeking knowledge from book, motivate seminar and others. In addition when people have master in their basic skills, they can build a solid foundation of their life and working with their goals setting, time management, their creativity and others. So from that they can look for opportunities to boost their confidence. Then by empower the personality people may help themselves to understand on how their life work and begin. By build the self esteem, self worth, mental discipline and the inner power it will help people to reduce their block to do something. Then people also suggest to find more meaning and purpose for their live by connect deeply with their objective or goals to grow themselves, institution, spirituals and others element.